2013
DOI: 10.1016/j.brainres.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise attenuates inhibitory avoidance memory deficit induced by paradoxical sleep deprivation in rats

Abstract: The deleterious effects of paradoxical sleep deprivation (SD) on memory processes are well documented. Physical exercise improves many aspects of brain functions and induces neuroprotection. In the present study, we investigated the influence of 4 weeks of treadmill aerobic exercise on both long-term memory and the expression of synaptic proteins (GAP-43, synapsin I, synaptophysin, and PSD-95) in normal and sleep-deprived rats. Adult Wistar rats were subjected to 4 weeks of treadmill exercise training for 35 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 77 publications
0
15
1
Order By: Relevance
“…Other studies suggested that treadmill exercise had neuroprotective effects on deleterious behavioral, synaptic and molecular changes induced by paradoxical sleep deprivation (Fernandes et al, 2013;Zagaar et al, 2012a,b). These investigations revealed that the benefits of exercise at the cellular level may be due to its capability to increase the production of BDNF and other signaling molecules in sleep-deprived male rats (Zagaar et al, 2012a,b).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies suggested that treadmill exercise had neuroprotective effects on deleterious behavioral, synaptic and molecular changes induced by paradoxical sleep deprivation (Fernandes et al, 2013;Zagaar et al, 2012a,b). These investigations revealed that the benefits of exercise at the cellular level may be due to its capability to increase the production of BDNF and other signaling molecules in sleep-deprived male rats (Zagaar et al, 2012a,b).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies offered that treadmill exercise had neuroprotective effects on detrimental behavioral, synaptic and molecular changes induced by sleep deprivation (Fernandes et al, 2013;Zagaar et al, 2013;Zagaar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover physical exercise improves many aspects of brain functions as well as induces neuroprotection [6].…”
Section: Introductionmentioning
confidence: 99%